2002
DOI: 10.1300/j064v19n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Microenvironmental Conditions Related to the Use of Synthetic Sheet Mulches for Protecting Newly Planted Trees in Semi-Arid Environments

Abstract: Microenvironmental conditions created by six weed control methods and the resulting survival and height growth of two species of windbreak trees were measured in three separate plantings in Nebraska. The treatments included three synthetic sheet mulches commonly used in tree plantings. Climagro, a black polyethylene mulch, and Sunbelt, a black woven polypropylene mulch, improved the growth of green ash (Fraxinus pennsylvanica Marsh.) in two of the three plantings. Survival of green ash and survival and growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Controlling weeds with mulches is probably the most environmentally safe way to provide weed control (Stepanek et al, 2002). Mulches may be inorganic, such as plastics or landscape fabrics, or organic, such as wood chips, straw, or hay.…”
Section: Establishment Phasementioning
confidence: 99%
“…Controlling weeds with mulches is probably the most environmentally safe way to provide weed control (Stepanek et al, 2002). Mulches may be inorganic, such as plastics or landscape fabrics, or organic, such as wood chips, straw, or hay.…”
Section: Establishment Phasementioning
confidence: 99%
“…Plants and organic materials have been recorded to be one of the major factors that affect soil aggregate stability (Six et al, 2004). Reports have shown that black polyethylene and black-woven polypropylene improved the structural stability of the soil by enhancing the growth of plants which is a source of organic material (Stepanek et al, 2002). Soil solarization techniques improve soil structure by creating favorable conditions for soil aggregation, through changes in soil water content and temperature thereby improving the efficient mineralization of soil organic matter (Green et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, concerns that herbicides may be toxic to people and the environment and may cause damage to young trees from herbicide drift. Recently, several silvicultural studies have shown that plastic (Davies, 1988;Walker and McLaughlin, 1989;Bendfeldt et al, 2001;Samyn and Vos, 2002;Stepanek et al, 2002;Green et al, 2003;Shirgure et al, 2003) and paper sheet mulches (Wooten and Helms, 1981;Zutter et al, 1987;Siipilehto, 2001) resulted in increased survival rates and more rapid growth depending on type of tree, location, weed competition and various environmental factors. One of the problems associated with the use of plastic mulches is the cost of removal and disposal from the field either prior to or after harvest, particularly in short-rotation tree farms.…”
Section: Introductionmentioning
confidence: 99%